DESIGN OF WIRELESS CONTROL SYSTEMS AND NAVIGATION SYSTEMS ON THE AUTONOMOUS VEHICLES AT HEAVY EQUIPMENT COMPANY - Suprapto, Heru; Nur Fauzi, Iqbal; Ardi, Syahril; Ponco, Agus (Technologic, 2022)
In this paper, the research development of the Autonomous Vehicle Prototype project has been carried out. The research was carried out on a golf cart (buggy) by designing wireless control and navigation systems. Designing a wireless control system on a golf cart aims to control the drive systems, steer systems, and brake systems. Furthermore, this system can be controlled electrically wirelessly through a Joystick Radio Controller, so that the golf cart can move forward, reverse, turn right and turn left. The navigation system aims to enable golf carts to track from point A to point B by using several sensors, including the GPS (Global Positioning System) sensor. GPS is used for tracking position on the golf cart, IMU (Inertia Measurement Unit) as a measure of the golf cart heading degree, LIDAR (Light Distance and Ranging) is used to detect distance and avoid obstacles, and Hall Effect Sensor as a speed sensor. The integration of the sensor and actuator systems is carried out using an Arduino Mega 2560 type microcontroller. Next, the movement from point A to point B is carried out autonomously. The final result of this research is that the GPS sensor can detect a track distance of 68.8 m with a minimum accuracy of 3 m and a resolution of 1 m. The IMU sensor can detect headings of 90o with 2o accuracy and 1o resolution. The LIDAR sensor can detect obstacles at a distance of 0 m – 4 m, and the Hall Effect sensor can detect the RPM of the car at a speed of 5 km/h. Golf cart control can be done wirelessly and automatically on the navigation system from point A to point B by avoiding obstacles.